The Effect of Alarm Use on the Awareness of Taking Iron Supplements (Haemoglobin Levels) as a Prevention of Haemorrhagic Postpartum - Firdaus, Lina Zahrotul; Setyowati, Lisus; Ermawati, Iit (Puslitbang Sinergis Asa Professional, 2023)
Anemia is one of the indirect causes of Postpartum Hemorrhage (HPP) during childbirth. The development of iron supplement alarm reminders can be used as an alternative intervention to increase awareness and consumption of iron supplements as a preventive measure against HPP. This study aims to analyze the Effect of Alarm Usage on Awareness in Consuming Iron Supplements (Hemoglobin Levels) as a Prevention of HPP in the Working Area of the Tempurejo Community Health Center, Jember Regency. The research employs a one-group pre-post-test design (pre-experiment) with a cross-sectional approach involving 30 respondents through Accidental Sampling. Data collection includes coding, editing, tabulation, and subsequent manual and computer-based analysis using Paired T-Test. Among the 30 respondents, the awareness of taking iron supplements before using the alarm showed non-compliance in 22 respondents (73.3%) and compliance in only 8 respondents (26.7%), with all 30 (100%) pregnant women experiencing anemia, either moderate (73.3%) or mild (26.7%). After the alarm was used, the number of respondents aware and compliant in taking iron supplements increased to 27 respondents (90%), with only 3 respondents (10%) remaining non-compliant. This was also indicated by an increase in normal Hb levels in 18 respondents (60%). The P-value was 0.000 and a = 0.05, meaning r < a, indicating the influence of alarm usage on awareness in consuming iron supplements (hemoglobin levels) as a preventive measure against HPP. This is crucial for pregnant women to regularly consume iron supplements for safe and healthy childbirth. Midwives should consistently remind pregnant women to consume a minimum of 90 supplements during pregnancy and adapt to technological advancements by using gadgets familiar to the community